2023
DOI: 10.7150/ijms.80543
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between endoscopic gastric abnormalities and colorectal polyps: a cross-sectional study based on 33439 Chinese patients

Abstract: Background: No study on the relationship between common abnormalities of the upper digestive tract and colorectal polyps (CPs) has been conducted. Methods: 33439 patients were enrolled in this cross-sectional study, of which 7700 had available Helicobacter pylori ( H.pylori ) information. All participants underwent colonoscopy and esophagogastroduodenoscopy (EGD) simultaneously or within six months at Tongji Hospital, Tongji Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…While they can appear anywhere in the stomach, they are most commonly found in the antrum and tend to be solitary [ 3 ]. They often occur in the background of atrophic gastritis and intestinal metaplasia, although there is no proven relationship with H. pylori infection [ 3 , 28 ]. In our study, one patient had gastric adenocarcinoma that developed based on an adenoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While they can appear anywhere in the stomach, they are most commonly found in the antrum and tend to be solitary [ 3 ]. They often occur in the background of atrophic gastritis and intestinal metaplasia, although there is no proven relationship with H. pylori infection [ 3 , 28 ]. In our study, one patient had gastric adenocarcinoma that developed based on an adenoma.…”
Section: Discussionmentioning
confidence: 99%
“…Feng et al found that the presence of stomach disorders such as GPs, H. pylori infection and atrophic gastritis increased the risk of colorectal polyps (CPs) ( p < 0.001). This relationship was found to be significant in both univariate and multivariate analyses [ 28 ]. The same study also stated that colorectal polyps were statistically more common in hyperplastic and fundic gland polyps [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several case-control and retrospective cohort studies have shown a substantial link between H. pylori infection and the prevalence of CP/CRC[ 14 - 17 ]. Similarly, cross-sectional studies conducted in various areas and nations consistently shown that H. pylori infection was an independent risk factor for CP, especially colorectal adenomatous polyp (CAP)[ 18 - 21 ]. Boustany et al [ 22 ] reported the first findings from a large population-based analysis of 47714750 people, establishing an independent link between a history of H. pylori infection and the risk of CRC.…”
Section: The Association Between H Pylori and Cp/crcmentioning
confidence: 99%